ANALISIS IMPLEMENTASI KEBIJAKAN SISTEM PENDIDIKAN BINTARA KEPOLISIAN NEGARA REPUBLIK INDONESIA DI SEKOLAH POLISI NEGARA POLDA BALI - I Ketut Suastika; Agus Joko Purwanto; Ade Reza Hariyadi (Jurnal Administrasi Pendidikan, 2022)
This research aims to determine the Implementation of Police Education System Policy at the Bali Police National Police SPN in the Implementation of Education for the Formation of Bintara Polri in 2021. Policy implementation analysis uses the theory of George C. Edward III, using four variables, communication, resources, disposition, and bureaucratic structure. This research used the qualitative descriptive, with the source informant head of SPN, PJU, Gadik and Pengasuh in the SPN environment of Bali Police. The role of communication is carried out from top to bottom, sideways and down to the top with good implementation. The role of human resources, budgets, equipment, and authorities in accordance with the directives (directions) carried out responsibly. The role of disposition can be seen from the implementation of SOP by SPN Polda Bali and through (warrant) signed above to be carried out in accordance with the responsibilities of all personnel. This bureaucratic structure can be seen from the readiness of the implementation of work exercises held in polres/polsek. The implementation of education at SPN Polda Bali is good and adequate but there needs to be increased certification for gadik and caregivers and needs to be coordinated location mapping early so that the implementation of work exercises runs well and systematically.